DEEP LEARNING IN THE BAMI ARABIC INSTRUCTION METHOD - Nasywa Alya Silmina Khoiri; Shofa Mushtofa Khalid (Universitas Islam Sumatera Utara (UISU), 2026)
Arabic language learning practices at Integrated Islamic Schools (SIT) are often dominated by textual memorization and formal grammatical rules, which frequently hinder the development of functional communication skills. This study analyzes the implementation of the BAMI Method (Bahasa Arab Metode Insantama) through a deep learning perspective, focusing specifically on the pedagogical transition from surface-level theory to functional conversation (hiwar). A qualitative approach with a reflective-phenomenological design was employed to capture the essence of the learning transformation. The research involved 20 participants, consisting of one Arabic language teacher and 19 female 11th-grade students at SMAIT Insantama Bogor. Data were gathered through semi-structured interviews, direct classroom observations, and questionnaires. Findings reveal that 78.9% (n=15) of students reported high satisfaction, correlating the method's success with the synergy between contextual teaching and the daily realities of boarding school life. Key results indicate that systematic scaffolding and mindful strategies, such as visual associations and oral exercises, accelerate the internalization of linguistic meaning more effectively. Concurrently, 36.8% (n=7) of students also noted facing challenges in independent practice due to psychological barriers like shyness and physical fatigue during morning sessions. This study concludes that the BAMI Method effectively aligns linguistic mastery with holistic deep learning principles. These findings suggest that integrating more joyful learning elements can further optimize student autonomy and interactive engagement in Arabic pedagogy.